2016
DOI: 10.1128/genomea.01263-16
|View full text |Cite
|
Sign up to set email alerts
|

Draft Genome Sequences of Biosafety Level 2 Opportunistic Pathogens Isolated from the Environmental Surfaces of the International Space Station

Abstract: The draft genome sequences of 20 biosafety level 2 (BSL-2) opportunistic pathogens isolated from the environmental surfaces of the International Space Station (ISS) were presented. These genomic sequences will help in understanding the influence of microgravity on the pathogenicity and virulence of these strains when compared with Earth strains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 10 publications
0
16
0
Order By: Relevance
“…Culture-based resistance assays had also previously indicated that the majority of both sets of strains were resistant to penicillin and some S. aureus strains were resistant to erythromycin and rifampin as well (29, 30). In the present work, we found that only penicillin resistance was significantly enriched in the ISS-associated S.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…Culture-based resistance assays had also previously indicated that the majority of both sets of strains were resistant to penicillin and some S. aureus strains were resistant to erythromycin and rifampin as well (29, 30). In the present work, we found that only penicillin resistance was significantly enriched in the ISS-associated S.…”
Section: Discussionmentioning
confidence: 93%
“…(C) Phylogenetic tree constructed from core gene codon alignment with midpoint rooting. ISS-, human-, and BE-E-sourced strains from the work of Checinska Sielaff et al (29) and the Wallace and Voorhies data set (Table S1) are shaded in blue, yellow, and gray, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Omics can also help obtain information about the persistence of viruses on the ISS so that effective techniques to detect those viruses and countermeasures for the safety of crew health can be developed.
Figure 3 TImeline of key space microbiology experiments An overview of the space microbiology experiments leading to Microbial Tracking (MT) experiments (MT-1 and MT-2) ( Be et al., 2017 ; Checinska Sielaff et al., 2017 ; Checinska Sielaff et al., 2016 ; Crabbe et al., 2013 ; Kim et al., 2013 ; Klaus and Howard, 2006 ; Knox et al., 2016 ; Singh et al., 2018b ; Taylor et al., 2014 ; Urbaniak et al., 2018 , 2020a ; Venkateswaran et al., 2017 ; Wilson et al., 2007 ; Yang et al., 2013b ). The figure has been generated using BioRender ( https://biorender.com/ ).
…”
Section: Future Directionsmentioning
confidence: 99%